Kryminalizacja finansowania terroryzmu w świetle przepisu art. 165a kodeksu karnego : część 2 - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The progressing globalization, the ease of movement, and the pace of information flow undoubtedly intensified the threat of terrorism, which is an important social issue. One of the crucial instruments in combating terrorist activity is counteracting its financing. The article analyzes the crime of financing terrorism, which has been defined in Art. 165a of the Polish Criminal Code. An attempt will be made to answer the question whether the legislative measures taken in the above-mentioned field are purposeful, necessary, and justified. The article also presents the genesis of the current legal regulations aimed at counteracting the financing of terrorism in the Polish Penal Code.
Keywords: terrorism; financing terrorism; terrorist act; terrorist activity; group crime